Obscure contract terms: An inadvertent pricing experiment - Stephen J. Choi; Mitu Gulati; Ugo Panizza; Robert E. Scott; W. Mark C. Weidemaier (Graduate Institute of International and Development Studies, 2024)
Contract terms that improve or reduce the likelihood of repayment of a debt should impact its price. That's basic economics. But what about a contract that is hundreds of pages long and has lengthy and complex terms that even the lawyers are unwilling to read? Believers in efficient markets might predict that variations that affect the likelihood of repayment in such obscure contract terms will be priced at the outset if there are profits to be made by exploiting these variations. An alternate view is that little attention is paid to the fine print in highly standardized contracts until the likelihood of default becomes sufficiently salient to make reading the fine print worthwhile. Using several inadvertent real-world experiments, we examine the question of how and when variations that are assumed to be standardized in obscure contract terms are priced.
Keywords: G14; K12; G12; 330; Contract complexity; Market efficiency; Sovereign Debt